Production Risk Analysis in Rice Farming in Surabaya City - Almeyda Ashfi Raihan; Hamidah Hendrarini; Risqi Firdaus Setiawan (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
Rice farming is an important sector in supporting national food security, especially in urban areas such as Surabaya, which faces various risks. This study aims to identify sources of production risk, analyze the level of production risk, and formulate strategies for rice farming production risk in Surabaya. The study was conducted in Surabaya because it is a metropolitan city with high rice consumption and rapid urbanization. This study used a quantitative descriptive approach with the fishbone diagram method to identify sources of production risk and the House of Risk (HOR) model to determine priorities and risk control strategies. Data was collected through questionnaires and interviews with 25 farmers in Jeruk Village, Lakarsantri District, Surabaya. The results showed that there were six sources of risk and three risk events. From the analysis conducted in HOR phase 1, there were 3 priority risk agents with the highest Aggregate Risk Potential (ARP) values, namely pests and diseases with an ARP value of 536.19, climate and weather with an ARP value of 526.95, and land ownership with an ARP value of 158.76. The control strategies recommended through Phase 2 of the HOR include 7 strategies that are expected to increase production yields, farmer income, and strengthen food security in Surabaya City.